PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN LITERASI DIGITAL MENUJU PENDIDIKAN BERKUALITAS PERSPEKTIF SDGs 2030 - Tia Lestari; Puput Putri Hidayah; Ichsan Fauzi Rachman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Digital literacy is a person's ability to use digital technology effectively and as well as possible. Digital literacy education is a very important education for this generation because in order to realize quality education from the SDGs 2030 perspective, to support digital literacy education the role of technology is needed. The method used in this research is Literature Review or literature review which is in the form of an explanation of a theory of discovery or a research topic, the explanation of these theories can be used as a theoretical basis. The results of this research are that digital technology and literacy play a very important role in supporting education and making it easier for teaching staff, students, even researchers and education to implement digital literacy more effectively and create quality education in accordance with SDGs goal number 4, even with digital literacy it is possible creating education that cares about the surrounding environment. Because as time goes by, more and more individuals are using technology for their daily lives and these two things cannot be separated. Keywords: Education, Digital Literacy, Technology, SDGs